An object-oriented approach for modelling and simulation of construction operations. (6th October 2008) - Zhang, H.; Tam, C.M.; Wang, J.Y.
This paper describes the application of an object-oriented (OO) modelling concept and OO programming mechanisms to develop an activity object-oriented (AOO) simulation strategy for modelling construction operations. The AOO simulation strategy considers construction activities to be objects, thus overcoming some pitfalls due to the general simulation strategies in developing simulation models or controlling simulation experiments. This paper also discusses the characteristics and related problems of some simulation strategies used for construction simulation. Moreover, the AOO graphical modelling interface associated with the AOO simulation strategy is described. Finally, the AOO simulation system has been compared with other simulation tools.